2006
DOI: 10.1177/1080569905285543
|View full text |Cite
|
Sign up to set email alerts
|

Building a Shared Virtual Learning Culture

Abstract: Business professionals increasingly use digital tools to collaborate across multiple cultures, locations, and time zones. Success in this complex environment depends on a shared culture that facilitates the making of knowledge and the best contributions of all team members. To prepare managers for such communication, the authors designed and implemented a semester-long intercultural virtual team project between a management communication course in the United States and one in Canada. To prevent faultlines betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(15 citation statements)
references
References 14 publications
(13 reference statements)
0
15
0
Order By: Relevance
“…Moreover, by engaging in a cross-cultural virtual collaboration, students facilitated work with counterparts from different cultural backgrounds, communication styles, and expectations. Similar to the learning outcomes of previous GNLEs (Starke-Meyerring & Andrews, 2006), developing students' intercultural sensitivity and intercultural communication competence was an essential objective in the outcome of this project.…”
Section: Learning Objectivesmentioning
confidence: 87%
“…Moreover, by engaging in a cross-cultural virtual collaboration, students facilitated work with counterparts from different cultural backgrounds, communication styles, and expectations. Similar to the learning outcomes of previous GNLEs (Starke-Meyerring & Andrews, 2006), developing students' intercultural sensitivity and intercultural communication competence was an essential objective in the outcome of this project.…”
Section: Learning Objectivesmentioning
confidence: 87%
“…Attempts to set up international collaborations between student groups from different countries have a long, growing history (Anderson, Bergman, Bradley, Gustafsson, & Matzke, 2010;Du-Babcock & Varner, 2008;Fitch, Kirby, & Greathouse Amador, 2008;Herrington, 2005Herrington, , 2008Herrington & Tretyakov, 2005;Kennon, 2008;Klein & La Berge, 2012;Moreno-Lopez, 2004;Stärke-Meyerring & Andrews, 2006;Thompson & Carter, 1973). An increasing body of research has demonstrated the benefits of having students learn international professional communication by working in CCVTs, linked through the Internet (Flammia, 2005(Flammia, , 2012Flammia, Cleary, & Slattery, 2010;Gerritsen & Verckens, 2006;Goby, 2007;Jarvenpaa & Leidner, 1999;Stärke-Meyerring, Duin, & Palvetzian, 2007).…”
Section: Managing Complexity: a Technical Communication Translation Cmentioning
confidence: 97%
“…Within this framework of goals, assignments, and tools, it was our hope that students would 'achieve the kind of transformative learning that results from inquiring into, questioning, and negotiating these diverse ways of knowing and from building shared learning and knowledge cultures across traditional boundaries' (Starke-Meyerring & Wilson, 2008, p. 21), having the impact described in the GNLE research (Starke-Meyerring & Andrews, 2006) and in the cultural psychology literature (Kitayama & Cohen, 2007).…”
Section: International Online Project Designmentioning
confidence: 96%